Synchronization and diversity in business cycles: a network analysis of the European Union - Matesanz Gómez, David (2016)
In this article, we use a correlation matrix and its internal networks to analyse business cycle synchronization across Europe since 2000. This methodology allows us to summarize individual country interactions and co-movements while also capturing the existing heterogeneity of connectivity within the European economic system. Our results indicate that synchronization of the euro zone countries remained stable from 1999 until the current financial crisis, after which co-movements increased sharply and synchronization rose to the highest in the time sample. By endogenously identifying clusters of countries with close connections in their business cycle, we also refute the commonly accepted notion of identifiable core and peripheral euro zone countries.